1976
DOI: 10.1177/00220345760550010901
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Properties of Human Enamel and Dentin

Abstract: Fracture in enamel is anisotropic with respect ot the orientation of the enamel rods, with Wf for fracture parallel to the rods being 0.3 X 10(2) J/meter2 but on the order of 2.0 X 10(2) J/meter2 for fracture perpendicular to the rods. Fractographs of enamel showed that the enamel rods behaved as integral units during controlled fracture. A model was proposed to explain the fracture properties of enamel involving the assumption that the hydroxyapatite crystals did not fracture but that their orientation determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
123
1
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(137 citation statements)
references
References 8 publications
8
123
1
2
Order By: Relevance
“…Indeed, ref. [8] does indicate that crack propagation perpendicular to the tubules is more energetically favorable, consistent with the absence of fiber bridging in that direction. However, excessive scatter in their results makes such definitive conclusions difficult; moreover, no direct evidence of such bridging was presented.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Indeed, ref. [8] does indicate that crack propagation perpendicular to the tubules is more energetically favorable, consistent with the absence of fiber bridging in that direction. However, excessive scatter in their results makes such definitive conclusions difficult; moreover, no direct evidence of such bridging was presented.…”
Section: Introductionmentioning
confidence: 69%
“…This highly oriented microstructure is believed to confer anisotropy to the mechanical properties, although the magnitude and orientation of the anisotropy is not well established. Indeed, after some five decades of research on the mechanical properties of dentin [e.g., [3][4][5][6][7][8][9][10][11][12][13][14][15], there is still little consistency in some of the basic questions that dictate its structural behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of enamel fracture have observed cracks more commonly along rod boundaries than running through rods (Ramussen et al 1976). Bridges of 10-20µm wide in enamel have been observed in several previous experimental studies (Bajaj and Arola, 2009a, 2009b; Bechtle et al, 2010a;Bajaj et al, 2008); they span across multiple rods.…”
Section: Discussionmentioning
confidence: 95%
“…Biomechanical tests are destructive and although they provide information about the bulk behavior of the tissue, they are unable to pinpoint areas of weaknesses within the tissue (Popowics et al, 2004). As these areas of weaknesses occur on a microstructural level (Rasmussen et al, 1976), they are inaccessible to traditional stress/ strain measurements (e.g., strain gauges). Here we present a new approach to overcome these difficulties.…”
mentioning
confidence: 99%